A scoping review on epidemiology and pathogenesis of death due to primary amoebic meningoencephalitis - Saraswathy, Krishneswari Rajasekharan Nair (International Journal Of Community Medicine And Public Health, 2024)
Primary amoebic meningoencephalitis (PAM) also known as Naegleriasis is a lethal central nervous system disorder caused by the amoeba Naegleria fowleri and spreads through contaminated water bodies. Nasal cavity is the route of entry for the infective form trophozoite. It is a fatal disease as the earlier diagnosis is missed due to its resemblance with Bacterial meningitis. This is a trial to record the pathogenesis of death due to PAM from available literatures. 22 research articles reported with death due to PAM had been reviewed and results documented. Out of 45 patients, most of them had contact with contaminated water bodies and all the investigations available showed cerebral oedema. Most of the cases had contact with contaminated water bodies which shows the need of decontamination of water bodies. Late diagnosis of most of the cases due to resemblance of symptoms with bacterial meningitis is also a cause for lethality.